2021
DOI: 10.3389/fnagi.2021.786337
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Alzheimer’s Disease and Parkinson’s Disease in Individuals With Osteoporosis: A Longitudinal Follow-Up Study Using a National Health Screening Database in Korea

Abstract: Background: Public health concerns regarding the potential link between osteoporosis and the increased occurrence of Alzheimer’s disease (AD) and Parkinson’s disease (PD) have been raised, but the results remain inconsistent and require further validation. Here, we investigated the long-term relationship of osteoporosis with the occurrence of AD/PD using data from a large-scale nationwide cohort.Methods: This longitudinal follow-up study included 78,994 patients with osteoporosis and 78,994 controls from the K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…However, vitamin D deficiency along with other endocrine, nutritional and iatrogenic factors may play an important role in bone mass depletion [ 63 ]. In a large longitudinal study including 78,994 patients with osteoporosis and 78,994 controls (from the Korean National Health Insurance Service-Health Screening Cohort database from 2002 to 2015), the first group disclosed a higher incidence of PD (Incidence: 2.4:1000 vs. 1.4:1000 in the control group), suggesting osteoporosis may be a risk factor for PD [ 64 ]. A similar result was reported by another study conducted on 23,495 individuals with osteoporosis compared with 23,495 controls, which revealed in the first group a significant higher risk of PD (HR 1.31, 95% CI, 1.13–1.50, p < 0.001).…”
Section: Role Of Vitamin D In Parkinson’s Diseasementioning
confidence: 99%
“…However, vitamin D deficiency along with other endocrine, nutritional and iatrogenic factors may play an important role in bone mass depletion [ 63 ]. In a large longitudinal study including 78,994 patients with osteoporosis and 78,994 controls (from the Korean National Health Insurance Service-Health Screening Cohort database from 2002 to 2015), the first group disclosed a higher incidence of PD (Incidence: 2.4:1000 vs. 1.4:1000 in the control group), suggesting osteoporosis may be a risk factor for PD [ 64 ]. A similar result was reported by another study conducted on 23,495 individuals with osteoporosis compared with 23,495 controls, which revealed in the first group a significant higher risk of PD (HR 1.31, 95% CI, 1.13–1.50, p < 0.001).…”
Section: Role Of Vitamin D In Parkinson’s Diseasementioning
confidence: 99%
“…Although we found no causal link between osteoporosis and AD, previous observational studies have shown a strong association between osteoporosis and AD. A cohort study found a 1.49-fold higher prevalence of AD in the osteoporosis group than in the control group after correcting for age and sex, and its results suggested that the presence of osteoporosis increases the potential for AD in adults over 40 years old ( Kwon et al, 2021 ). Another cohort study also found that osteoporosis was positively associated with cognitive and functional decline and that subjects with BMD values in the lowest quartile had a 2-fold increased risk of AD transition compared to controls ( Zhou et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis was designated as ICD-10 codes M80 (osteoporosis with pathological fracture), M81 (osteoporosis without pathological fracture), and M82 (osteoporosis in diseases classified elsewhere) [ 25 , 26 ]. Amongst them, we chose only people who underwent more than two times treatments in basis upon the bone density test of X-ray or computed tomography (Claim code: HC341-HC345, E7001-E7004) [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%